Qiyam al-Da’wah Fi Syi’ri “Man ‘Arafa” Li Hamzah Fansu>ri> - Sulfikar,; Fitriani, Laily; Al-Anshory, Abdul Muntaqim (Shaut al Arabiyyah, 2024)
Poetry is a concrete form of literary output to express human thoughts and feelings and is used as a medium for preaching in the process of spreading Islam. This study aims to determine the meaning contained in the poem "Man 'Arafa" by Hamzah Fansuri and to understand the interpretation of the da'wah value in the poem through a semiotic approach. This research uses a type of qualitative research through the method of library research (library research). Sources of data in this study are primary data and secondary data. The primary data is Man Arafa's poetry, while the secondary data is in the form of books, articles, research reports, and so on related to research. Data collection uses the documentation method, namely by reading and studying Hamzah Fansuri's poetry, and writings related to research. The data analysis technique used the descriptive method by describing the results of the identification through a semiotic approach. The results of the study show that the da'wah message contained in Man Arafa's poem is an invitation to draw closer to God which can be done in several ways, namely, recognizing oneself, recognizing God's substance and His attributes, increasing dhikr to remember God's power and greatness. by saying praises, increasing worship, good deeds, distancing oneself from actions that are not permitted by Allah, and always remembering death. Thus, humans always take care of the earth, guard their lives to remind themselves, stay in God's way, and avoid worldly things, by studying religious knowledge in earnest.